2016
DOI: 10.3855/jidc.6790
|View full text |Cite
|
Sign up to set email alerts
|

spa typing and antimicrobial resistance of Staphylococcus aureus from healthy humans, pigs and dogs in Tanzania

Abstract: Introduction: Staphylococcus aureus is an opportunistic pathogen causing infections in humans and animals. Here we report for the first time the prevalence of nasal carriage, spa typing and antimicrobial resistance of S. aureus in a Tanzanian livestock community. Methodology: Nasal swabs were taken from 100 humans, 100 pigs and 100 dogs in Morogoro Municipal. Each swab was enriched in Mueller Hinton broth with 6.5% NaCl and subcultured on chromogenic agar for S. aureus detection. Presumptive S. aureus colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The present systematic review assessed the overall prevalence of antibiotic-resistant bacterial strains isolated from dogs in Africa and found that many strains were multidrug resistant to most common and current used antibiotics (ampicillin, ampicillin/cloxacillin, tetracycline, penicillin, amoxicillin, cotrimoxazole, chloramphenicol and ciprofloxacin) used in humans (Okpara et al 2018). The high resistance of S. aureus strains to ampicillin found in dogs was also observed in humans (100.0%) and pigs (100.0%) in Tanzania by Katakweba et al (2016). But for tetracycline, resistance is moderate in humans (45.5%) and pigs (50.0%) in Tanzania, whilst it is high in dogs.…”
Section: Discussionmentioning
confidence: 87%
“…The present systematic review assessed the overall prevalence of antibiotic-resistant bacterial strains isolated from dogs in Africa and found that many strains were multidrug resistant to most common and current used antibiotics (ampicillin, ampicillin/cloxacillin, tetracycline, penicillin, amoxicillin, cotrimoxazole, chloramphenicol and ciprofloxacin) used in humans (Okpara et al 2018). The high resistance of S. aureus strains to ampicillin found in dogs was also observed in humans (100.0%) and pigs (100.0%) in Tanzania by Katakweba et al (2016). But for tetracycline, resistance is moderate in humans (45.5%) and pigs (50.0%) in Tanzania, whilst it is high in dogs.…”
Section: Discussionmentioning
confidence: 87%
“…The POT methods have been applied to study nosocomial epidemics of MRSA, showing a high discriminatory power [86,87]. Although strategies using molecular genotyping have been able to successfully detect the presence of SA infection, they are expensive compared to standard culture methods [82][83][84][85][86][87][88][89][90][91][92]. In this scenario, the development of a reliable laboratory method that can be readily adopted by general diagnostics laboratories to improve and accelerate the capacity of these tests is increasingly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates identified as Gram-positive cocci were spread on slides, and 3% H 2 O 2 (Sigma, H3410) was dropped on them. Gas bubble-forming, catalase-positive bacteria were recognized as staphylococci (20). Finally, isolates previously purified by incubating at 37°C for 24 hours on blood agar medium (Himedia, M001) were identified using an automated system (Phoenix 100, BD Diagnostic Systems, USA).…”
Section: Methodsmentioning
confidence: 99%